Imported malaria among people who travel to visit friends and relatives: is current UK policy effective or does it need a strategic change? - Behrens, R; Neave, P; Jones, C (BioMed Central, 2015)
The proportion of all imported malaria reported in travellers visiting friends and relatives (VFRs) in the UK has increased over the past decade and the proportion of Plasmodium falciparum malaria affecting this group has remained above 80% during that period. The epidemiological data suggest that the strategies employed in the UK to prevent imported malaria have been ineffective for VFRs. This paper attempts to identify possible reasons for the failure of the malaria prevention strategy among VFRs and suggest potential alternatives.A review of the current UK malaria prevention guidelines was undertaken and their approach was compared to the few data that are available on malaria perceptions and practices among VFRs.The current UK malaria prevention guidelines focus on educating travellers and health professionals using messages based on the personal threat of malaria and promoting the benefits of avoiding disease through the use of chemoprophylaxis. While malaria morbidity disproportionately affects VFRs, the mortality rates from malaria in VFRs is eight times, and severe disease eight times lower than in tourist and business travellers. Recent research into VFR malaria perceptions and practices has highlighted the complex socio-ecological context within which VFRs make their decisions about malaria. These data suggest that alternative strategies that move beyond a knowledge-deficit approach are required to address the burden of malaria in VFRs.Potential alternative strategies include the use of standby emergency-treatment (SBET) for the management of fevers with an anti-malarial provided pre-travel, the provision of rapid diagnostic testing and treatment regimen based in general-practitioner surgeries, and urgent and walk-in care centres and local accident and emergency (A&E;) departments to provide immediate diagnosis and accessible ambulatory treatment for malaria patients. This latter approach would potentially address some of the practical barriers to reducing the burden of malaria in VFRs by moving the process nearer to the community.